Data Ethics in Practice: Challenges and Opportunities for a Data Ethics Policy Function in the Public Sector - Domagala, Natalia (Journal of Leadership, Accountability and Ethics, 2021)
The overarching aim of data ethics is to promote responsible and sustainable use of data and its products for the benefit of people and society. Through an analysis of various approaches to data and AI ethics in the public sector, this paper aims to identify key goals and challenges for a data ethics policy function and provide recommendations. The paper connects the practical experience of data ethics professionals and the emerging theory through combining a literature review with primary data gathered during workshops with practitioners in the United Kingdom. It finds that key challenges for data ethics in the public sector include the lack of accountability of data ethics tools, lack of skills and awareness, the saturated landscape of ethical guidance, and insufficient diversity in the field. Opportunities and recommendations include: embedding data ethics in data science processes; providing a platform that collates the available ethical guidance; developing data ethics courses for public sector data scientists; establishing a data ethics community; increasing transparency in hiring and introducing extensive diversity measures.